Development and pilot evaluation of a personalized decision support intervention for low risk prostate cancer patients - Jeffrey Belkora; June M. Chan; Matthew R. Cooperberg; John Neuhaus; Lauren Stupar; Tia Weinberg; Jeanette M. Broering; Imelda Tenggara; Janet E. Cowan; Stan Rosenfeld; Stacey A. Kenfield; Erin L. Van Blarigan; et al. (Cancer Medicine, 2020)
Abstract Objectives Development and pilot evaluation of a personalized decision support intervention to help men with early‐stage prostate cancer choose among active surveillance, surgery, and radiation. Methods We developed a decision aid featuring long‐term survival and side effects data, based on focus group input and stakeholder endorsement. We trained premedical students to administer the intervention to newly diagnosed men with low‐risk prostate cancer seen at the University of California, San Francisco. Before the intervention, and after the consultation with a urologist, we administered the Decision Quality Instrument for Prostate Cancer (DQI‐PC). We hypothesized increases in two knowledge items from the DQI‐PC: How many men diagnosed with early‐stage prostate cancer will eventually die of prostate cancer? How much would waiting 3 months to make a treatment decision affect chances of survival? Correct answers were: “Most will die of something else” and “A little or not at all.” Results The development phase involved 6 patients, 1 family member, 2 physicians, and 5 other health care providers. In our pilot test, 57 men consented, and 44 received the decision support intervention and completed knowledge surveys at both timepoints. Regarding the two knowledge items of interest, before the intervention, 35/56 (63%) answered both correctly, compared to 36/44 (82%) after the medical consultation (P = .04 by chi‐square test). Conclusions The intervention was associated with increased patient knowledge. Data from this pilot have guided the development of a larger scale randomized clinical trial to improve decision quality in men with prostate cancer being treated in community settings.